On the Vocabulary Used in an Inferior Style in the Poems of Modern Poets - Шульская, О. В. (Kalbotyra, 1992)
The functions of the vocabulary used in an inferior style get complicated due to the change in the norms of the author’s narration. The creative usage of the colloquial language and jargon is closely connected with the pecularities of an individual style.